Barriers and facilitators to primary care staff conducting research – a qualitative systematic review - Zoe Edwards; Michael Tatterton (European Journal of General Practice)
Background Research is vital for progress and development of healthcare and may help relieve current health service pressures through improvements and efficiencies. Research in primary care is not well established and is not part of routine practice. This study aims to investigate the barriers and facilitators to primary care staff conducting research.Method A systematic literature review was conducted in CINAHL, Medline, APA, PsycInfo, AHMED and EMBASE from inception to April 2023. Searches were for studies involving clinical or non-clinical staff working in primary care where barriers or facilitators to conducting research were examined.Results Twenty-one studies were included from 2000 to 2022. The QuADs quality appraisal method found that papers were of varying, often low quality. Five themes were found – research beliefs & understanding, time, funding & recognition, skills & knowledge, administration & support, ethics & understanding and communication & people. Staff thought research useful but optional and were impeded by time and funding. They need training and support to carry out research. Communication from the researchers before, during and after study completion would prevent problems and lead to more research participation in the future.Conclusion Improved communication at all stages would serve as a facilitator to primary care staff conducting research. Clear, appropriate training for all staff would allow them to complete appropriate tasks for their roles and prevent one individual taking full responsibility. Embedding research in primary care with protected time and resources to complete it would remove barriers to taking part.